Secularization Theory and Religion. Issue 1 (March 2021) - Dhima, Kostanca; Golder, Matt
Abstract: What is the relationship between religion and human development? Using data from the pooled 1981–2014 World and European Values Surveys, we examine the effect of human development on a country's level of religious attendance and belief. Consistent with the idea that the primary causal mechanism underlying secularization theory has to do with the substitutability of secular and religious goods, we find that human development has a negative effect on religious attendance but no effect on religious belief. Our results indicate that as societies develop, we should not be surprised if religious belief remains high even as religious attendance declines. The negative effect of human development on religious attendance is driven primarily by a country's level of education and health. Our analysis suggests that it is important to think carefully about what one's theoretical model of the secularization process implies for different aspects of religion.